1983
DOI: 10.2307/1541476
|View full text |Cite
|
Sign up to set email alerts
|

FEEDING STRUCTURES, BEHAVIOR, AND MICROHABITAT OF ECHINOCYAMUS PUSILLUS (ECHINOIDEA: CLYPEASTEROIDA)

Abstract: In the Firth of Lorne, Scotland, Echinocyamus pusillus was found most abundantly in highly variable, poorly sorted substrates at depths of 10-20 m. It was common in areas exposed to extensive wave and tidal current activity, but absent in fine sediments in sheltered areas. In size, feeding mechanism, and behavior, the species is highly adapted for nestling in the interstices between relatively large pebbles. The feeding mechanism is atypical for clypeasteroids: substrate particles with attached organisms are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
(31 reference statements)
2
34
0
Order By: Relevance
“…Occurrence in deep-water environments has been reported for the minute clypeasteroid Echinocyamus. This echinoid shows a wide geographical and ecological distribution ranging from tropical to temperate regions, where it lives from shallow water to a depth of 1250 m (Tortonese 1965;Telford et al 1983;Nebelsick and Kowalewski 1999;Zavodnik 2003;Degraer et al 2006;Grun et al 2014). Further, the sand dollar Echinarachnius parma, which occurs in the north Atlantic and Pacific, extends from the intertidal zone to depths of about 1600 m (Mortensen 1948b;Ellers and Telford 1984).…”
Section: Comparison Of Clypeasteroid Echinoid Deposits From Sardiniamentioning
confidence: 99%
“…Occurrence in deep-water environments has been reported for the minute clypeasteroid Echinocyamus. This echinoid shows a wide geographical and ecological distribution ranging from tropical to temperate regions, where it lives from shallow water to a depth of 1250 m (Tortonese 1965;Telford et al 1983;Nebelsick and Kowalewski 1999;Zavodnik 2003;Degraer et al 2006;Grun et al 2014). Further, the sand dollar Echinarachnius parma, which occurs in the north Atlantic and Pacific, extends from the intertidal zone to depths of about 1600 m (Mortensen 1948b;Ellers and Telford 1984).…”
Section: Comparison Of Clypeasteroid Echinoid Deposits From Sardiniamentioning
confidence: 99%
“…Telford et al (1983) showed that it most commonly occurs in substrates exposed to intensive wave and tidal activity, and exposure to strong currents seems an essential requirement. The common occurrence of E. pusillus in facies D and E therefore seems to indicate that these sediments were derived from shallow water above the fair-weather base.…”
Section: Cape Arkhangelos Calcarenite (Facies a To E)mentioning
confidence: 99%
“…Märkel et al (1977) distinguished the grinding lantern of the Clypeasteroida from the gripping lantern of the regular echinoids. The teeth of the tiny fibulariid Echinocyamus pusillus chew ingested food (Telford et al 1983). Lovén (1892) noted the distinctive changes that occur in the highly modified Aristotle's lantern of sand dollars, which include compression and a pentagonal star shape with unequal sides and lantern structures.…”
Section: Figmentioning
confidence: 99%